Technical and tactical performance differences according to player`s nationality and playing position in the Chinese Football Super League - Gai, Y.; Volossovitch, A.; Lago, C.; Gómez, M. Á. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was to identify the key performance indicators related to technical and tactical aspects according to playing position (defender, midfielder and forward) and nationality in the Chinese Football Super League (CSL). Data were collected from 240 matches (n = 200 players) played by 16 teams during the 2016 season. Match performance data were gathered by OPTA Sports Company from 2,364 observations that included domestic (n = 1081) and foreign players (n = 1,283). All comparisons were analysed using the nonclinical magnitude-based inferences (MBI). The analyses of 49 variables related to passing and attack organization, defense and goal scoring showed significant differences between domestic and foreign players when analyzing each playing position. Therefore, the current study provides match performance profiles that can be used by coaches in order to improve the recruitment process and team composition regarding players` nationality.